Calculate the air-gap magnetic field of tubular permanent magnet linear motor base on equivalent surface current model. (1st January 2014) - Huang, Ke-feng; Li, Huai-shu; Zhou, Yu
The air-gap magnetic field is an important design parameter for tubular permanent magnet linear motor including surface-mounted PMs (TPMSLM), as it significantly influences the thrust force capability and efficiency. Based on the results indicate that the existing analytical research methods of the air-gap magnetic field is not accurate. This tool has calculated the air-gap magnetic field of the current-carrying coil. Next, the analytic formula of air-gap magnetic field of the motor is derived from the equivalent surface current model. In order to verify the validity and accuracy of the proposed method, we took approximately a TPMSLM to analyse it. The results show that: the analytical method and finite element method to calculate the air-gap magnetic field were both in good agreement. The proposed motor air-gap magnetic field method is quick, effective, and had a high accuracy rate.